ASSESSING KNOWLEDGE REGARDING BASIC LIFE SUPPORT AMONG HEALTH CARE PROFESSIONALS WORKING AT TERTIARY CARE HOSPITALS IN DISTRICT SWAT (Journal of Medical & Health Sciences Review, 2025)
Basic Life Support (BLS) refers to the fundamental medical assistance provided by trained individuals like emergency medical technicians in situations where advanced medical care is not readily accessible. The primary goal is to stabilize a critically ill person. BLS training teaches participants how to rapidly recognize severe life-threatening conditions, carry out effective chest compressions, deliver appropriate breathing assistance, and promptly use automated external defibrillators (AEDs).(2) A majority of the participants, around 58.3%, displayed a lack of proper understanding regarding Basic Life Support (BLS). On average, doctors achieved a score of 53.5%, dentists scored 43.3%, and nurses scored 38.4%. The research also indicated that doctors, those with prior BLS training experience, and individuals who graduated 6 to 10 years ago were more likely to possess sufficient knowledge of BLS, as revealed through a thorough analysis of the data.(4) Adequate knowledge of BLS was shown by only 12%, 55% had a moderate level of knowledge, and 32% had insufficient knowledge